DAMPAK HUKUM PERUBAHAN NAMA PADA IDENTITAS ANAK TERHADAP HAK-HAK KEPERDATAAN - Robby Bagus Indrawan; Risti Dwi Ramasari (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
The Unitary State of the Republic of Indonesia is one of the countries that by law is obliged to provide legal protection and certainty to its citizens, one of the legal protections provided by the government is the protection of children by regulating it in Law 23 of 2002 on Child Protection as amended by Law No. 35 of 2014 on Amendments to Law No. 23 of 2002 on Protection of Children.  Child. Every child is entitled to survival, growth, and development and is entitled to protection from violence and discrimination, set out in the Constitution of the Republic of Indonesia 1945 Article 28B paragraph 2. Man born in this world carries rights to himself, it is stipulated in Article 2 of the Civil Code which states that "the child in the womb of a woman, is regarded as having been presumed where, if also the interests of the child will it and die s birth, it is considered this never existed